2016
DOI: 10.7566/jpsj.85.115001
|View full text |Cite
|
Sign up to set email alerts
|

Valence State in CeIrIn5 at High Magnetic Fields of up to 42 T

Abstract: High-magnetic-field X-ray absorption spectroscopy of the heavy-fermion compound CeIrIn 5 has been conducted to clarify the valence state of Ce at the metamagnetic transition. The field-induced change in the X-ray absorption spectrum near the Ce-L 3 edge is found to be smaller than the resolution limit of the measurement, suggesting that no field-induced valence change larger than 0.005 takes place at 2 K up to 42 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The previous studies suggested that fluctuations of magnetic moment and valence of Ce atom are important for SC in CeIrIn 5 [14,15], however, it is controversial. X-ray absorption experiment in high-field revealed that Ce valence state does not change up to H ′ m ∼ 42 T [19]. In the vicinity of magnetic QCP, some Ce compounds such as CeRhIn 5 shows a field-induced magnetic transition above the critical pressure, where the magnetic transition temperature is suppressed to 0 K [20].…”
Section: Phase Diagrammentioning
confidence: 98%
“…The previous studies suggested that fluctuations of magnetic moment and valence of Ce atom are important for SC in CeIrIn 5 [14,15], however, it is controversial. X-ray absorption experiment in high-field revealed that Ce valence state does not change up to H ′ m ∼ 42 T [19]. In the vicinity of magnetic QCP, some Ce compounds such as CeRhIn 5 shows a field-induced magnetic transition above the critical pressure, where the magnetic transition temperature is suppressed to 0 K [20].…”
Section: Phase Diagrammentioning
confidence: 98%